Preparation method of biodegradable sanitary water-absorbing material

Cellulose nanofibers were prepared by selective oxidation with TEMPO and reverse suspension polymerization. By combining surface crosslinking technology and zwitterionic monomers, the problems of weak gel network strength and poor antibacterial properties of cellulose-based SAP were solved, resulting in a biodegradable, highly absorbent and antibacterial sanitary absorbent material suitable for high-end hygiene products.

CN121005831APending Publication Date: 2025-11-25SHANDONG YANQUAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511356189.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing superabsorbent polymers are difficult to biodegrade, and the modified cellulose-based SAP gel network has weak strength, is prone to gel blockage, and has poor antibacterial properties. Traditional preparation processes are energy-intensive and produce irregular products, making it difficult to meet the needs of high-end hygiene products.

Method used

Cellulose nanofibers were prepared by selective oxidation with TEMPO and high-pressure homogenization. Combined with reverse suspension polymerization and surface crosslinking technology, zwitterionic monomers and antibacterial agents were introduced to construct a uniform microsphere structure, achieving biodegradability, antibacterial properties and high water absorption of the material.

Benefits of technology

A high-strength, uniformly shaped biodegradable absorbent material was prepared, which has excellent water absorption, antibacterial properties and environmental friendliness, making it suitable for industrial production and improving the comfort and safety of hygiene products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121005831A_ABST
    Figure CN121005831A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional cellulose materials, and particularly relates to a preparation method of a biodegradable sanitary water absorbing material. The preparation method comprises the following steps: by taking cellulose nanofibrils prepared by oxidizing TEMPO as a reinforcing skeleton, carrying out ultraviolet-initiated polymerization on the cellulose nanofibrils, acrylic acid and a functional monomer in a reversed-phase suspension system, and then carrying out surface crosslinking treatment, so as to prepare a spherical granular product. The product disclosed by the invention has high water absorption rate, high gel strength, excellent antibacterial and bacteriostatic performance and full biodegradability, is suitable for the field of high-end hygienic products, is simple and efficient in process flow, and is easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of functional cellulose materials, and particularly relates to a preparation method of a biodegradable sanitary water-absorbing material. BACKGROUND

[0002] High molecular water-absorbing resin (SAP) is a kind of organic material with a three-dimensional network structure of slight cross-linking, which can absorb and lock hundreds or even thousands of times of water of its own weight, and is widely used in the fields of sanitary products such as baby diapers, women's sanitary products and adult incontinence pads. At present, most of the commercially available SAP products are prepared by solution polymerization or suspension polymerization using petroleum-based acrylic acid and its salts as monomers. Although such synthetic SAP has excellent liquid absorption performance, its molecular chain structure is stable and is difficult to be degraded by microorganisms in the natural environment.

[0003] To address the above environmental problems, the development of biodegradable SAP has become a current research hotspot. Among them, the preparation of SAP from natural polymers such as cellulose, starch and chitosan is one of the most promising directions. Cellulose is widely available, renewable and completely biodegradable, and is rich in hydroxyl groups on the molecular chain, which is easy to modify. In the prior art, the high water absorption of the modified cellulose-based SAP is usually achieved by etherification (such as carboxymethyl cellulose) or graft copolymerization with synthetic monomers. However, such materials face two technical bottlenecks: first, the gel network strength of the modified cellulose-based SAP is generally weak, and the "gel blocking" phenomenon easily occurs after absorbing liquid, which leads to a decrease in absorption rate and liquid backflow, affecting the use experience; second, in order to achieve the water absorption rate required for commercial application, a high proportion of non-degradable synthetic polymer chains need to be introduced, which in turn sacrifices the overall degradability of the material.

[0004] In addition, sanitary products are in direct contact with human skin, and the antibacterial and bacteriostatic performance of the material is strictly required. The prior art usually adds organic antibacterial agents or silver ion antibacterial agents in the post-processing stage of the product, but there are problems such as easy precipitation, poor durability, high cost or potential toxicity. How to integrate efficient and safe antibacterial function in situ in the degradable polymer network while not compromising its absorption performance and environmental friendly characteristics is a technical challenge.

[0005] In terms of preparation process, the traditional bulk polymerization-pulverization route has high energy consumption and long process, and the obtained product particles have irregular shape and wide size distribution, which is easy to produce dust and may affect the comfort of use. Although the reverse phase suspension polymerization technology can be used to prepare regular microspheres SAP, this process has significant differences in process parameters (such as oil-water ratio, dispersant selection, polymerization stability, etc.) from the traditional petroleum-based system in the preparation of biobased degradable SAP, and lacks targeted technical solutions.

[0006] Therefore, it has important practical significance and application value to develop a new sanitary water-absorbing material with excellent comprehensive performance, green and efficient process, good biodegradability and antibacterial performance, so as to meet the growing market demand of high-end sanitary products and solve the pressure on the environment. SUMMARY

[0007] In view of the deficiencies of the prior art, the purpose of the present application is to provide a preparation method of biodegradable sanitary water-absorbing material. The biodegradable sanitary water-absorbing material prepared by the present application has good water absorption, water retention rate, biodegradability and good antibacterial performance, and has good application prospect in the field of health.

[0008] The present application provides a preparation method of biodegradable sanitary water-absorbing material, comprising the following steps:

[0009] S1, add broadleaf wood pulp into deionized water and stir, add 2,2,6,6-tetramethylpiperidine oxide and sodium bromide, and stir for 20-40 min; slowly add sodium hypochlorite solution in 4℃ ice water bath, and the dropwise adding time is controlled for 28-32 min; under the condition of normal temperature and stirring, add sodium hydroxide solution to adjust pH to 10, and add 10 mL of anhydrous ethanol; centrifuge the reaction mixture at 8000 rpm for 15 min, transfer the supernatant containing oxidized cellulose nanofilament to a dialysis bag with a molecular weight cut-off of 10-14 kDa, dialyze with deionized water for 72 h, dilute the dialysis purified oxidized cellulose nanofilament dispersion to a solid content of 1-2 wt%, and homogenize under a pressure of 800 bar for 10 times to obtain a modified fiber gel dispersion;

[0010] As a preferred technical scheme of the present application, in step S1, the broadleaf wood pulp is broadleaf wood pulp after sulfite bleaching; the concentration of the sodium hypochlorite solution is 4.8-5.2 mol / L.

[0011] As a preferred technical scheme of the present application, in step S1, the use amount ratio of the broadleaf wood pulp, deionized water, 2,2,6,6-tetramethylpiperidine oxide, sodium bromide, sodium hypochlorite solution and anhydrous ethanol is (4.8-5.2) g:(180-220) mL:0.08 g:0.8 g:32 mL:(9-11) mL.

[0012] As a preferred technical scheme of the present application, in step S1, the dialysis operation needs to be ended until the conductivity of dialysis water is less than 5 muS / cm.

[0013] S2, stirring acrylic acid under ice-salt bath at -5-0℃, slowly adding sodium hydroxide solution, controlling the dropping speed to keep the system temperature below 15℃, sequentially adding N,N'-methylene-bis-acrylamide, sulfobetaine methacrylate, phenol red and zinc nitrate, continuously stirring for 35-45min to obtain a premix solution;

[0014] As a preferred technical scheme of the present application, in step S2, the mass fraction of sodium hydroxide is 38-42%.

[0015] As a preferred technical scheme of the present application, in step S2, the mass ratio of acrylic acid, sodium hydroxide solution, N,N'-methylene-bis-acrylamide, sulfobetaine methacrylate, phenol red and zinc nitrate is (34-38):90:(0.16-0.2):(3.4-3.8):(0.034-0.038):1.8.

[0016] S3, mixing white oil and Tween 80 at room temperature, stirring for 20-40min to obtain an oil phase liquid;

[0017] As a preferred technical scheme of the present application, in step S3, the dosage ratio of white oil and Tween 80 is 100mL:1g.

[0018] S4, mixing the modified fiber gel dispersion prepared in step S1, the premix solution prepared in step S2 and photoinitiator 184 under nitrogen atmosphere, stirring for 2min, quickly pouring the obtained mixed aqueous phase into the oil phase liquid prepared in step S3, stirring for 15min at room temperature, stopping the nitrogen flow, turning on the ultraviolet light irradiation for 30min, separating the obtained reaction mixture by suction filtration, washing and drying to obtain polymer gel microspheres;

[0019] As a preferred technical scheme of the present application, in step S4, the volume ratio of modified fiber gel dispersion, premix solution and oil phase liquid is 2:13:45.

[0020] As a preferred technical scheme of the present application, in step S4, the mass ratio of modified fiber gel dispersion and photoinitiator 184 is 20:0.18.

[0021] S5, dissolving ethylene glycol diglycidyl ether and aluminum sulfate in a 50% mass fraction ethanol solution, stirring to obtain a surface crosslinking agent solution, uniformly spraying the surface crosslinking agent solution onto the surface of the polymer gel microspheres, vacuum drying at 100-120℃ for 35-45min, cooling, sealing and moisture-proof packaging to obtain biodegradable sanitary water-absorbing materials.

[0022] As a preferred technical scheme of the present application, in the step S5, the amount ratio of ethylene glycol diglycidyl ether, aluminum sulfate, ethanol solution and polymer gel microspheres is 0.5 g:0.5 g:(18-22) mL:(18-22) g.

[0023] Compared with the prior art, the present application has the following beneficial effects:

[0024] (1) The present application successfully prepares cellulose nanofibril (CRF) with high aspect ratio and abundant surface carboxyl groups from natural broadleaf wood pulp by combining TEMPO selective oxidation with high-pressure homogenization treatment, which is introduced into the polymer network as a three-dimensional reinforcing skeleton, effectively improving the mechanical strength and structural stability of the material through hydrogen bonding and ionic bonding, overcoming the shortcomings of poor gel strength of traditional superabsorbent resin, and providing the final product with environmental friendly characteristics in the whole life cycle due to its natural biodegradability.

[0025] (2) The present application innovatively uses inverse suspension polymerization process to successfully realize the morphological control of the product from irregular block to uniform microspheres by accurately controlling the ratio of oil and water, the concentration of dispersant and the shear force. This process is one-step forming, which eliminates the high-energy drying, crushing and screening steps in the traditional process, simplifies the production process, reduces the production cost, and the obtained spherical product has smooth surface, fast absorption rate, high comfort, and is more suitable for industrial large-scale production.

[0026] (3) The present application introduces zwitterionic monomer sulfobetaine methacrylate (SBMA) and zinc nitrate into the polymerization system, which gives the material excellent anti-biofouling and broad-spectrum antibacterial dual functions. The hydration layer constructed by SBMA can effectively resist the adhesion of proteins and bacteria, maintaining the cleanliness of the material surface and the efficient absorption channel; zinc nitrate provides safe and long-acting antibacterial ability, and the two work together to significantly improve the hygiene safety and use reliability of the material in health and medical applications.

[0027] (4) The present application integrates intelligent pH responsive components and double surface crosslinking technology to comprehensively improve the function and performance of the product. The pH indicator (phenol red) gives the material a visual infection warning ability, increasing the intelligent properties of the product; and the spray surface crosslinking based on ethylene glycol diglycidyl ether and aluminum sulfate constructs a dense interpenetrating network layer on the surface of the microspheres, further enhancing the liquid retention capacity, abrasion resistance and dimensional stability of the product, making the finally prepared biodegradable sanitary water-absorbing material have excellent comprehensive performance and wide application prospect. BRIEF DESCRIPTION OF DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed for the embodiment description will be briefly introduced as follows.

[0029] Figure 1 The surface morphology of the biodegradable sanitary water-absorbing material prepared in Example 1 under a scanning electron microscope (SEM) is shown in the following figure. DETAILED DESCRIPTION

[0030] For the purpose of understanding the present application, the present application is illustrated by the following examples. It should be apparent to those skilled in the art that the examples are only for the purpose of understanding the present application and should not be considered as specific limitations to the present application.

[0031] Example 1

[0032] A method for preparing a biodegradable sanitary water-absorbing material, comprising the following steps:

[0033] S1, 5 g of sulfite bleached broadleaf wood pulp was weighed into 200 mL of deionized water, stirred for 2 h, 0.08 g of 2,2,6,6-tetramethylpiperidine oxide and 0.8 g of sodium bromide were added, and stirred for 30 min; 32 mL of 5 mol / L sodium hypochlorite solution was slowly added in an ice water bath at 4℃, and the dropping time was controlled for 30 min; 0.5 M sodium hydroxide solution was added to adjust the pH to 10 under stirring at 25℃, and 10 mL of anhydrous ethanol was added; the reaction mixture was centrifuged at 8000 rpm for 15 min, and the supernatant containing oxidized cellulose nanofibrils was transferred to a dialysis bag with a molecular weight cut-off of 12 kDa, and dialyzed with deionized water for 72 h until the conductivity of the dialysis water was less than 5 μS / cm; the dialysis-purified oxidized cellulose nanofibril dispersion was diluted to a solid content of 1.5 wt%, and was subjected to homogenization treatment at 800 bar for 10 times to obtain a modified fiber gel dispersion;

[0034] S2, 36 g of acrylic acid was stirred at 300 rpm under an ice-salt bath at -5℃, 90 g of 40% sodium hydroxide solution was slowly added, the dropping speed was controlled to keep the system temperature below 15℃, 0.18 g of N,N'-methylenebisacrylamide, 3.6 g of sulfobetaine methacrylate, 0.036 g of phenol red and 1.8 g of zinc nitrate were added in sequence, and the stirring was continued for 40 min to obtain a premix;

[0035] S3, 200 mL of white oil and 2 g of Tween 80 were mixed at room temperature and a stirring speed of 400 rpm, and stirred for 30 min to obtain an oil phase liquid;

[0036] S4, 20 g of the modified fiber gel dispersion prepared in step S1, 130 g of the premix prepared in step S2 and a photoinitiator 184 were mixed under a nitrogen atmosphere, stirred for 2 min, the obtained mixed aqueous phase was quickly poured into 450 g of the oil phase liquid prepared in step S3, stirred at room temperature for 15 min, the nitrogen supply was stopped, and the ultraviolet light irradiation was turned on for 30 min with a wavelength of 365 nm and a power of 250 W. The obtained reaction mixture was separated by suction filtration, washed with 200 mL of anhydrous ethanol for 3 times, and dried at 60 °C for 2 h to obtain the polymer gel microspheres;

[0037] S5, 0.5 g of ethylene glycol diglycidyl ether and 0.5 g of aluminum sulfate were dissolved in 20 mL of a 50% ethanol solution to obtain a surface crosslinking agent solution, which was uniformly sprayed onto the surface of 20 g of the polymer gel microspheres, and then the mixture was placed in a vacuum drying oven at 120 °C for 40 min. After cooling, the mixture was sealed and moisture-proof packaged to obtain the biodegradable sanitary water-absorbing material.

[0038] Example 2

[0039] S1, 5.2 g of sulfite bleached broadleaf wood pulp was added to 220 mL of deionized water, stirred for 2 h, and then 0.08 g of 2,2,6,6-tetramethylpiperidine oxide and 0.8 g of sodium bromide were added, and stirred for 30 min. A 32 mL solution of sodium hypochlorite with a concentration of 5 mol / L was slowly added dropwise in an ice water bath at 4 °C, and the dropwise time was controlled for 30 min. A 0.5 M sodium hydroxide solution was added dropwise under stirring at 25 °C to adjust the pH to 10, and 11 mL of anhydrous ethanol was added. The reaction mixture was centrifuged at 8000 rpm for 15 min, and the supernatant containing the oxidized cellulose nanofibrils was transferred to a dialysis bag with a molecular weight cut-off of 12 kDa. The dialysis was carried out with deionized water for 72 h until the conductivity of the dialysate was less than 5 μS / cm. The dialysis-purified oxidized cellulose nanofibril dispersion was diluted to a solid content of 1.5 wt%, and then homogenized at a pressure of 800 bar for 10 times to obtain a modified fiber gel dispersion;

[0040] S2, 38 g of acrylic acid was stirred at a speed of 300 rpm under an ice-salt bath at -5 °C, and a 90 g sodium hydroxide solution with a mass fraction of 40% was slowly added dropwise. The dropwise speed was controlled to keep the system temperature below 15 °C at all times. Then, 0.2 g of N,N'-methylenebisacrylamide, 3.8 g of sulfobetaine methacrylate, 0.038 g of phenol red and 1.8 g of zinc nitrate were added in sequence. The stirring was continued for 40 min to obtain a premix;

[0041] S3, 200 mL of white oil and 2 g of Tween 80 were mixed at room temperature with a stirring speed of 400 rpm for 30 min to obtain an oil phase liquid;

[0042] S4, 20 g of the modified fiber gel dispersion prepared in step S1, 130 g of the premix prepared in step S2 and a photoinitiator 184 were mixed under a nitrogen atmosphere, stirred for 2 min, the obtained mixed aqueous phase was quickly poured into 450 g of the oil phase liquid prepared in step S3, stirred at room temperature for 15 min, the nitrogen supply was stopped, and the ultraviolet light irradiation was turned on for 30 min with a wavelength of 365 nm and a power of 250 W. The obtained reaction mixture was separated by suction filtration, washed with 200 mL of anhydrous ethanol for 3 times, and dried at 60℃ for 2 h to obtain the polymer gel microspheres;

[0043] S5, 0.5 g of ethylene glycol diglycidyl ether and 0.5 g of aluminum sulfate were dissolved in 22 mL of a 50% ethanol solution to obtain a surface crosslinking agent solution, which was uniformly sprayed onto the surface of 22 g of the polymer gel microspheres, and then the mixture was placed in a vacuum drying oven at 120℃ for 40 min. After cooling, the mixture was sealed and moisture-proof packaged to obtain the biodegradable sanitary water-absorbing material.

[0044] Example 3

[0045] S1, 4.8 g of sulfite bleached broadleaf wood pulp was added to 180 mL of deionized water, stirred for 2 h, and then 0.08 g of 2,2,6,6-tetramethylpiperidine oxide and 0.8 g of sodium bromide were added, and stirred for 30 min. A 32 mL solution of sodium hypochlorite with a concentration of 5 mol / L was slowly added dropwise in an ice water bath at 4℃, and the dropwise time was controlled for 30 min. A 0.5 M sodium hydroxide solution was added dropwise under stirring at 25℃ to adjust the pH to 10, and 9 mL of anhydrous ethanol was added. The reaction mixture was centrifuged at 8000 rpm for 15 min, and the supernatant containing the oxidized cellulose nanofibrils was transferred to a dialysis bag with a molecular weight cut-off of 12 kDa. The dialysis was carried out with deionized water for 72 h until the conductivity of the dialysate was less than 5 μS / cm. The dialysis-purified oxidized cellulose nanofibril dispersion was diluted to a solid content of 1.5 wt%, and then homogenized at a pressure of 800 bar for 10 times to obtain a modified fiber gel dispersion;

[0046] S2, 34 g of acrylic acid was stirred at a speed of 300 rpm under an ice-salt bath at -5℃, and a 90 g sodium hydroxide solution with a mass fraction of 40% was slowly added dropwise. The dropwise speed was controlled to keep the system temperature below 15℃ at all times. Then, 0.16 g of N,N'-methylenebisacrylamide, 3.4 g of sulfobetaine methacrylate, 0.034 g of phenol red and 1.8 g of zinc nitrate were added in sequence. The stirring was continued for 40 min to obtain a premix;

[0047] S3, 200 mL of white oil and 2 g of Tween 80 were mixed at room temperature with a stirring speed of 400 rpm for 30 min to obtain an oil phase liquid;

[0048] S4, 20 g of the modified cellulose gel dispersion prepared in step S1, 130 g of the premix prepared in step S2 and a photoinitiator 184 were mixed under a nitrogen atmosphere, stirred for 2 min, the obtained mixed aqueous phase was quickly poured into 450 g of the oil phase liquid prepared in step S3, stirred at room temperature for 15 min, the nitrogen was stopped, and the ultraviolet light irradiation was started for 30 min with a wavelength of 365 nm and a power of 250 W. The obtained reaction mixture was separated by suction filtration, washed with 200 mL of anhydrous ethanol for 3 times, and dried at 60 °C for 2 h to obtain the polymer gel microspheres;

[0049] S5, 0.5 g of ethylene glycol diglycidyl ether and 0.5 g of aluminum sulfate were dissolved in 18 mL of an ethanol solution with a mass fraction of 50%, stirred to obtain a surface crosslinking agent solution, and uniformly sprayed onto the surface of 18 g of the polymer gel microspheres. The mixture was placed in a vacuum drying oven at 120 °C for 40 min, cooled, sealed and moisture-proof packaged to obtain the biodegradable sanitary water-absorbing material.

[0050] Comparative Example 1

[0051] The difference between this comparative example and Example 1 is that the modified cellulose gel dispersion prepared in step S1 is not used. In step S4, only 130 g of the premix prepared in step S2 is used for inverse suspension polymerization with 450 g of the oil phase liquid, and the remaining steps and parameters are the same as those in Example 1.

[0052] Comparative Example 2

[0053] The difference between this comparative example and Example 1 is that the same amount of deionized water is used to replace the sulfobetaine methacrylate in step S2. That is, no zwitterionic functional monomer is added in the premix, and the remaining steps and parameters are the same as those in Example 1.

[0054] Comparative Example 3

[0055] The difference between this comparative example and Example 1 is that the inverse suspension polymerization process is not used, but bulk polymerization is used instead. Specifically, in step S4, after 20 g of the modified cellulose gel dispersion and 130 g of the premix are mixed, the mixture is not poured into the oil phase, but is directly placed in a mold for bulk polymerization under nitrogen protection and ultraviolet light irradiation to obtain a hydrogel. The hydrogel is dried in a forced air drying oven at 60 °C to a constant weight, mechanically pulverized, sieved (20-40 mesh), and then subjected to the surface crosslinking of step S5.

[0056] Comparative Example 4

[0057] The difference between this comparative example and Example 1 is that no surface crosslinking agent is used in step S5. That is, step S5 is omitted, and the polymer gel microspheres obtained in step S4 are directly subjected to final drying and packaging.

[0058] The biodegradable sanitary water-absorbing materials prepared in the above examples and comparative examples were tested, and the testing methods were as follows:

[0059] I. Water Absorption Ratio

[0060] According to GB / T 22875-2018, the tea bag method was adopted. 0.05 g (W1) of dry sample was weighed and placed in a tea bag, immersed in 500 mL of 0.9wt% NaCl solution, and after 30 min, it was taken out and hung to no longer drip, and the total weight of the tea bag (W2) was weighed. The water absorption ratio (g / g) = (W2-W1-W0) / W1, wherein W0 is the mass of the tea bag before water absorption. Three parallel tests were taken for the average value.

[0061] II. Pressurized Absorption Capacity

[0062] According to EDANA WSP 241.2.R3 (15), in the specified device, the sample was allowed to absorb 0.9wt% NaCl solution under 0.7psi (about 4.83kPa) pressure for 1h, and the mass of the liquid absorbed per unit mass of the sample (g / g) was calculated.

[0063] III. Antibacterial Rate

[0064] According to GB / T 20944.3-2008, the shaking method was adopted. After 0.5g of sample was shaken with 5mL of bacterial suspension (Staphylococcus aureus, concentration 1×10 5 CFU / mL) in a conical flask for 1h, the liquid was taken for viable bacterial count.

[0065] Antibacterial rate (%) = (A-B) / A x 100%;

[0066] Wherein A is the average number of bacteria of the blank sample, and B is the average number of bacteria of the sample.

[0067] IV. Gel Strength

[0068] A texture analyzer (TA.XT Plus) was used for testing. After the liquid-saturated gel was placed on the test platform, a cylindrical probe (P / 0.5) was used to press down to the gel rupture at a speed of 1mm / s, and the maximum force at the moment of rupture (unit: g) was recorded.

[0069] V. Biodegradation Rate

[0070] According to GB / T 19277.1-2011, the aerobic biodegradation capacity test was carried out by composting method. The carbon dioxide release amount of the sample within 90 days was determined at 58℃, and the percentage relative to the theoretical carbon dioxide production was calculated.

[0071] The performance test data are shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] Conclusion: From the data in Table 1, it can be concluded that the products prepared in Examples 1-3 of the present application have the best comprehensive performance, i.e. they have high water absorbency, very high antibacterial rate, excellent pressurized absorption capacity and gel strength, and good biodegradability. The performance defects of the comparative examples confirm that the CRF enhanced skeleton, the SBMA functional monomer, the inverse suspension polymerization process and the surface crosslinking treatment are all indispensable key technical features of the present application.

Claims

1. A method for producing a biodegradable sanitary water-absorbing material, characterized by, Comprising the following steps: S1, add broadleaf wood pulp into deionized water and stir, add 2, 2, 6, 6-tetramethylpiperidine oxide and sodium bromide, stir for 20-40 min; in 4℃ ice water bath, drop sodium hypochlorite solution, drop time control for 28-32 min; under normal temperature, stirring conditions, drop sodium hydroxide solution to adjust pH to 10, add anhydrous ethanol; centrifuge the reaction mixture at 8000 rpm for 15 min, transfer the supernatant containing oxidized cellulose nanofibrils to a dialysis bag with a molecular weight cut-off of 10-14 kDa, dialysis, dilute the oxidized cellulose nanofibril dispersion after dialysis and purification to a solid content of 1-2 wt%, homogenize to obtain modified fiber gel dispersion; S2, stir acrylic acid under-5-0℃ ice salt bath, slowly drop sodium hydroxide solution, control the drop speed to make the system temperature always below 15℃, add N, N'-methylene bisacrylamide, sulfobetaine methacrylate, phenol red and zinc nitrate in turn, continue to stir for 35-45 min, obtain a premix; S3, mix white oil and Tween 80 at room temperature, stir for 20-40 min, obtain oil phase liquid; S4, mix the modified fiber gel dispersion prepared in step S1, the premix prepared in step S2 and photoinitiator 184 under nitrogen atmosphere, stir for 2 min, quickly pour the obtained mixed aqueous phase into the oil phase liquid prepared in step S3, stir at room temperature for 15 min, stop nitrogen, turn on ultraviolet light for 30 min, separate, wash and dry the obtained reaction mixture to obtain polymer gel microspheres; S5, dissolve ethylene glycol diglycidyl ether and aluminum sulfate in 50wt% ethanol solution, stir to obtain surface crosslinking agent solution, uniformly spray on the surface of polymer gel microspheres, vacuum dry at 100-120℃ for 35-45 min, cool, seal and moisture-proof package to obtain biodegradable sanitary water-absorbing material.

2. The method of producing a biodegradable sanitary water-absorbing material according to claim 1, characterized by: In the step S1, the broadleaf wood pulp is the broadleaf wood pulp after sulfite bleaching; the concentration of the sodium hypochlorite solution is 4.8-5.2 mol / L.

3. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S1, the amount ratio of the broadleaf wood pulp, deionized water, 2, 2, 6, 6-tetramethylpiperidine oxide, sodium bromide, sodium hypochlorite solution and anhydrous ethanol is (4.8-5.2) g:(180-220) mL:0.08 g:0.8 g:32 mL:(9-11) mL.

4. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S1, the dialysis operation should be ended until the dialysate conductivity is less than 5 μS / cm.

5. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S2, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 38-42%.

6. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S2, the mass ratio of acrylic acid, sodium hydroxide solution, N, N'-methylene bisacrylamide, sulfobetaine methacrylate, phenol red and zinc nitrate is (34-38):90:(0.16-0.2):(3.4-3.8):(0.034-0.038):1.

8.

7. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S3, the amount ratio of white oil and Tween 80 is 100 mL:1 g.

8. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S4, the volume ratio of the modified fiber gel dispersion liquid, the premix liquid and the oil phase liquid is 2:13:

45.

9. The biodegradable sanitary water-absorbing material according to claim 1, characterized by: In the step S4, the mass ratio of the modified fiber gel dispersion liquid and the photoinitiator 184 is 20:0.

18.

10. The method for preparing a biodegradable sanitary absorbent material according to claim 1, characterized in that: In the step S5, the dosage ratio of the ethylene glycol diglycidyl ether, the aluminum sulfate, the ethanol solution and the polymer gel microspheres is 0.5 g:0.5 g:(18-22) mL:(18-22) g.